2019
DOI: 10.1002/aet2.10370
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Contemporary Clerkship: Theory‐based Educational Trial of Videos Versus Lectures in Medical Student Education

Abstract: Background: Despite increasing use of the flipped classroom (FC) technique in undergraduate medical education, the benefit in learning outcomes over lectures is inconsistent. Best practices in preclass video design principles are rarely used, and it is unclear if videos can replace lectures in contemporary medical education. Methods:We conducted a prospective quasi-experimental controlled educational study comparing theorybased videos to traditional lectures in a medical student curriculum. Medical students en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 42 publications
(57 reference statements)
1
8
0
Order By: Relevance
“…A Korean nationwide survey revealed that teaching videos increased students' subjective feelings of competence and were rated to be useful in different medical disciplines [25]. With respect to objective learning outcomes, studies comparing video-based against traditional teaching methods have reported divergent results with either improved theoretical practical knowledge [37,52,53], no effect differences [35] or even worse learning outcomes [36]. With respect to videobased ultrasound teaching, only two studies yet exist that have evaluated objective learning outcomes or students' acceptance, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Korean nationwide survey revealed that teaching videos increased students' subjective feelings of competence and were rated to be useful in different medical disciplines [25]. With respect to objective learning outcomes, studies comparing video-based against traditional teaching methods have reported divergent results with either improved theoretical practical knowledge [37,52,53], no effect differences [35] or even worse learning outcomes [36]. With respect to videobased ultrasound teaching, only two studies yet exist that have evaluated objective learning outcomes or students' acceptance, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Before first use in our study, the videos were repeatedly tested by selected medical students in order to optimize didactics specifically required by the target audience of ultrasound unexperienced medical students. Implementation of these principles aim at reducing cognitive load and enhancing learning which has been shown to improve objective learning outcomes when compared to traditional lectures [33,34,52]. However, one may speculate that the design principles may rather influence objective than subjective learning outcomes and acceptance among individuals with different learning preferences, respectively [52,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our small group, case-based discussions used a flipped classroom model, an effective and recommended modality for virtual instruction. [16][17][18][19][20][21][22] All small-group facilitators were reminded of the best practices for online, small group teaching, 23 which included use of introductions, learner-directed questioning to encourage equal participation, and "nudging" -reminders for learners to actively participate (See Appendix B).…”
Section: Objectivesmentioning
confidence: 99%
“…Alkhalaileh et al [10] emphasised that e-learning reduces the time required for CPR training compared to the conventional approach when the content is well-defined and focused. In addition, several studies based on an experimental design measuring knowledge retention by comparing blended or full online e-learning training with traditional CPR face-to-face training have shown that e-learning leads to knowledge comparable to that acquired through traditional training [4,[13][14][15]. However, none of these studies used e-learning to supplement face-to-face training.…”
Section: Introductionmentioning
confidence: 99%